Polish Listening SPAN: A new tool for measuring verbal working memory - Zychowicz, Katarzyna; Biedroń, Adriana; Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2017)
Individual differences in second language acquisition (SLA) encompass differences in working memory capacity, which is believed to be one of the most crucial factors influencing language learning. However, in Poland research on the role of working memory in SLA is scarce due to a lack of proper Polish instruments for measuring this construct. The purpose of this paper is to discuss the process of construction and validation of the Polish Listening Span (PLSPAN) as a tool intended to measure verbal working memory of adults. The article presents the requisite theoretical background as well as the information about the PLSPAN, that is, the structure of the test, the scoring procedures and the steps taken with the aim of validating it.